Implementasi Peraturan Menteri Keuangan Nomor 122 Tahun 2023 Tentang Petunjuk Pelaksanaan Lelang: Studi Kasus KPKNL Surakarta - Nurul Itsna Fawzi’ah; Widi Nugrahaningsih; Aris Prio Agus Santoso (International Forum of Researchers and Lecturers, 2025)
An auction is an open sales mechanism that provides the public with the opportunity to acquire goods or assets through the highest bid. This process begins with an official announcement and is carried out transparently. In line with the development of information technology and efforts to modernize public services, the Indonesian government issued Minister of Finance Regulation (PMK) Number 122 of 2023 concerning Auction Implementation Guidelines. This regulation aims to update and simplify the auction process with a digital approach to make it more effective, efficient, and reach the wider community. This study aims to analyze the implementation of PMK 122/2023 at the Surakarta State Assets and Auction Service Office (KPKNL) and identify obstacles encountered in its implementation. The research method used is a juridical-empirical with a qualitative approach, where primary data was obtained through interviews with auction officials and related staff at the Surakarta KPKNL, while secondary data was collected from regulations, official documents, and legal literature. The research results show that the implementation of PMK 122/2023 has had a positive impact on improving the quality of auction services through digitalization, such as the implementation of an e-Auction system, the provision of e-Auction Corner facilities, and the use of other information technology to facilitate public access. Based on Soerjono Soekanto's theory of legal implementation, the success of policy implementation is influenced by factors such as legal substance, law enforcement officers, and the legal culture of the community. The Surakarta KPKNL (National Public Service Agency) is considered successful in increasing efficiency, accountability, and service satisfaction to the community. However, obstacles remain in its implementation, such as disputes over ownership of auction objects, resistance to occupants' evictions, and technical and administrative challenges in using online systems. This research recommends the need for inter-agency synergy, strengthening complementary regulations, and public education to support the smooth and sustainable implementation of digital-based auctions.